2004
DOI: 10.2174/1381612043382693
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Coumarins and Coumarin-Related Compounds to Determine their Therapeutic Role in the Treatment of Cancer

Abstract: The Benzopyrones are a group of compounds whose members include coumarins and flavonoids. Dietary exposure to benzopyrones is quite significant, as these compounds are found in vegetables, fruit, seeds, nuts, coffee, tea and wine. It is estimated that the average western diet contains approximately 1 g/day of mixed benzopyrones. It is, therefore, not difficult to see why extensive research into their pharmacological and therapeutic properties is underway over many years. Coumarin is a natural substance that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
231
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(243 citation statements)
references
References 67 publications
0
231
0
2
Order By: Relevance
“…Some coumarins display cytostatic properties while others have cytotoxic activities (2). Their inhibitory eff ect on cell proliferation was confi rmed in various carcinoma cell lines, including those of melanoma, leukaemia, renal carcinoma, prostate and breast cancer (1,(3)(4)(5). This activity was further validated by other investigators in human subjects as well (6,7).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Some coumarins display cytostatic properties while others have cytotoxic activities (2). Their inhibitory eff ect on cell proliferation was confi rmed in various carcinoma cell lines, including those of melanoma, leukaemia, renal carcinoma, prostate and breast cancer (1,(3)(4)(5). This activity was further validated by other investigators in human subjects as well (6,7).…”
mentioning
confidence: 75%
“…The reagents used for this purpose include DNA intercalating agents, topoisomerase inhibitors, cytoskeleton-disrupting agents and antimetabolites. Among these coumarin and coumarin-related compounds, members of the benzo-α-pyrone family, have been proven to exert antitumour eff ects and cause signifi cant changes in the regulation of immune responses, cell growth and diff erentiation (1). Antitumour activity is believed to be due to coumarin metabolites (e.g., 7-hydroxycoumarin).…”
mentioning
confidence: 99%
“…Later, many other types of biological activities were discovered ranging from photosensitization to vasodilatation. Coumarin derivatives reported to exert anticancer activity through kinase targeting include esculetin (36), scopoletin (37) and daphnetin (38, Table 4) [77][78][79][80].…”
Section: Coumarinsmentioning
confidence: 99%
“…Esculetin (36) has been shown to induce apoptosis in various human cancer cells [77] and, more particularly, U937 human leukemia cells [78]. This anticancer activity was associated with selective activation of the phosphorylation of extracellular-regulated kinase (ERK) and c-Jun Nterminal kinase (JNK) [78].…”
Section: Coumarinsmentioning
confidence: 99%
“…A recent study has shown that 7-hydroxycoumarin inhibited the release of cyclin D1, which is overexpressed in many cancer types [13]. Many compounds derived from coumarin have numerous therapeutic applications, which include photochemotherapy, antitumor and anti-HIV therapy [14].…”
Section: Discussionmentioning
confidence: 99%